Las chullpas incas en las quebradas Ucriamayo Y Tulpaisa, Caylloma, Arequipa - Correa-Trigoso, Denis E. (2021)
In the immediate vicinity of the Mining Unit (M. U.) Tambomayo are located the Ucriamayo and Tulpaisa streams; and associated to these geographical areas, the archeological surveys Gentilmach’ay and Pushkanawasi were registered through archeological exploration. The area is located in the upper part of the Colca Valley (area of influence of the Collagua ethnic group), in the district of Tapay, province of Caylloma, department of Arequipa. The sites correspond to chullparia structures with the presence of cultural material, such as fragments of ceramics, plant remains, textiles, animal and human bone. The cultural affiliation of the ceramic material is Inca and the cultural modification of a skulls is observed. Both sites have particularities that suggest the existence of social differences of individuals buried in different environments. According to the evidences registered, different investigations with the cultural material registered in both archaeological sites are proposed.